2019
DOI: 10.1152/jn.00071.2019
|View full text |Cite
|
Sign up to set email alerts
|

Reduced blood oxygen levels induce changes in low-threshold motor unit firing that align with the individual’s tolerance to hypoxia

Abstract: This study aimed to quantify how acute hypoxia impacts firing characteristics of biceps brachii motor units (MUs) during sustained isometric elbow flexions. MU data were extracted from surface electromyography (EMG) during 25% maximal voluntary contractions (MVC) in 10 healthy subjects (age 22 ± 1 yr). Blood oxygen saturation (SpO2) was then stabilized at 80% by reducing 1% of the fraction of inspired oxygen every 3 min for 35 min. MU data were once again collected 1 h and 2 h following the 35-min desaturation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
0
9
1
Order By: Relevance
“…The emergence of enhanced excitability across the entire protocol suggests that the impact of reduced SnormalpO2 on corticospinal pathways is substantial during acute hypoxia. Although the present study identified a ubiquitous enhancement in corticospinal excitability, this contrasts with previous hypoxia studies that have identified a 2–3 h delay in motor unit firing changes (McKeown et al., 2019) and corticospinal excitability changes of the lower limb (Rupp et al., 2012). Likewise, adaptations in neural excitability were evident only when performing MVC, which is contrary to previous research examining the lower limb (Rupp et al., 2012).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The emergence of enhanced excitability across the entire protocol suggests that the impact of reduced SnormalpO2 on corticospinal pathways is substantial during acute hypoxia. Although the present study identified a ubiquitous enhancement in corticospinal excitability, this contrasts with previous hypoxia studies that have identified a 2–3 h delay in motor unit firing changes (McKeown et al., 2019) and corticospinal excitability changes of the lower limb (Rupp et al., 2012). Likewise, adaptations in neural excitability were evident only when performing MVC, which is contrary to previous research examining the lower limb (Rupp et al., 2012).…”
Section: Discussioncontrasting
confidence: 99%
“…A reduction in blood oxygenation can significantly impair the neural activation of muscles across a range of contraction tasks (Billaut et al., 2013; Goodall, Gonzalez‐Alonso, Ali, Ross, & Romer, 2012; McKeown, Simmonds, & Kavanagh, 2019; Ruggiero, Yacyshyn, Nettleton, & McNeil, 2018). Given that descending drive to muscles is modulated by supraspinal and spinal circuits, several studies have profiled these areas of the nervous system in response to acute exposure to hypoxia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2012; McKeown et al . 2019, 2020). SnormalpO2 and heart rate were monitored at all times using a pulse oximeter (Model 7500; Nonin Medical Inc., Plymouth, MN, USA) attached to the middle finger of the left hand.…”
Section: Methodsmentioning
confidence: 99%
“…As sensitivity to altered oxygen availability is quite variable between individuals (Rojas-Camayo et al 2018), F IO 2 was titrated over a 15 min period for each individual at a rate of 0.01 F IO 2 every 1.5 min and remained at the desired F IO 2 that consequently resulted in 80% S pO 2 for the 2 h experimental protocol. This hypoxic stimulus was chosen as previous research has documented hypoxia-induced changes in neuromuscular fatigue at similar S pO 2 levels (75-80%; Goodall et al 2010Goodall et al , 2012Ruggiero et al 2018) and durations of exposure (2-3 h; Rupp et al 2012;McKeown et al 2019McKeown et al , 2020. S pO 2 and heart rate were monitored at all times using a pulse oximeter (Model 7500; Nonin Medical Inc., Plymouth, MN, USA) attached to the middle finger of the left hand.…”
Section: Experimental Designmentioning
confidence: 99%